2014
DOI: 10.5694/mja13.11082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Rural Clinical School of Western Australia on work location of medical graduates

Abstract: Participation in the RCSWA is strongly associated with greater likelihood of working rurally. Graduates from urban backgrounds who participated in the RCSWA were much more likely to work in rural areas than those who did not. These data substantiate the RCSWA as an effective rural workforce strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
114
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 14 publications
14
114
6
Order By: Relevance
“…We confirm that one in four rural origin students return to work rurally 3 . However, we provide the first evidence that rural origin students do not 'return home'.…”
Section: Discussionsupporting
confidence: 73%
“…We confirm that one in four rural origin students return to work rurally 3 . However, we provide the first evidence that rural origin students do not 'return home'.…”
Section: Discussionsupporting
confidence: 73%
“…3 However, the impact of these 'rural exposures' vary according to the length of the placement and other factors unique to the placement itself. Students who voluntarily undertake these longer-term rural placements through rural clinical schools view the placements positively 8 and are more likely to practice in rural locations following graduation, [9][10][11][12][13] although these results may be due to selection bias rather than the placement itself. The longer the placement, the higher the intent to practice rurally.…”
mentioning
confidence: 46%
“…Studies of exposure to rural communities during medical studies have later shown how this leads to a greater tendency to work in these areas after graduation (14).…”
Section: Discussionmentioning
confidence: 99%